Fourth Ghana Economic Update : Enhancing Financial Inclusion - World Bank Group (World Bank, Washington, DC, 2019)
Ghana’s real gross domestic product (GDP) expanded in 2018, albeit at a slower rate than in 2017; the expansion was spurred by the mineral component of the industry sector. The government sustained its fiscal consolidation efforts in 2018 despite challenges. The current account deficit narrowed further in 2018 but portfolio capital outflows put pressure on reserves. The financial sector in Ghana has grown rapidly since 2010, and with it the share of Ghanaians with access to formal financial services, which is a measure of financial inclusion. Despite all the challenges in building a more financially inclusive economy, there has been a significant growth in the number of financial access points over the past five years. The government has facilitated interoperability across payment instruments by establishing a mobile money switching solution. But more can be done to leverage innovative digital technology, as is recognized in the government’s national financial inclusion and development strategy (NFIDS). In support of the government’s efforts, the financial sector analysis in this economic update concludes with five specific recommendations for enhancing financial inclusion in Ghana: digitize government and utility payments; link informal channels with formal financial services; promote agent banking; improve financial capability; and leverage data to improve access to finance.